Effects of short carbon fiber content on microstructure and mechanical property of short carbon fiber reinforced Nb/Nb5Si3 composites. (March 2019) - Xiong, Bowen; Wang, Zhenjun; Wang, Chaowei; Xiong, Yangziyi; Cai, Changchun
Abstract: The short carbon fiber reinforced Nb/Nb5 Si3 composites were innovatively fabricated by ball milling and spark plasma sintering. The effects of short carbon fiber contents (0.50 wt. %, 1.0 wt. %, 1.5 wt. % and 2.0 wt. %) on the microstructure and mechanical property of short carbon fiber reinforced Nb/Nb5 Si3 the composites were investigated. The results show that the content of interfacial phase Nb4 C3 increases with the increase of short carbon fiber content. Compared to the matrix Nb/Nb5 Si3, the mechanical properties of the composites are improved significantly owing to the addition of short carbon fiber. It is found that the increase of short carbon fiber content contributes to the enhancement of Vickers hardness, ultimate tensile strength and fracture toughness of the composites. The fracture surfaces are characterized by interface debonding and fiber pull-out, which indicate that a medium bonding strength of the interface between fiber and matrix was obtained in this composite. The interface debonding and fiber pull-out behavior play the important role in the fracture process, which are the dominant toughening mechanisms of the short carbon fiber reinforced Nb/Nb5 Si3 composites. Highlights: The Csf reinforced Nb/Nb5 Si3 composites with high density and dispersed Csf were fabricated. The Csf content affects the forming of interface phase Nb4 C3 . The Csf content affects the mechanical property of Csf reinforced Nb/Nb5 Si3 composite.